An Ecoflex-encapsulated interlayer-structured triboelectric nanogenerator for Sports activity monitoring - Haojie Yang; Zhongyang Xu; Zixuan Liu; Yifei Lu; Yonggeng Wei; Yong Shi (Energy Conversion and Management: X)
Incorporating self-powered devices with flexible sensors not only tackles the power obstacles linked to wearable electronics but also greatly broadens their capability and application fields. Triboelectric nanogenerator (TENG) have garnered significant interest in the wearable electronics sector because of their distinct ability to harness ambient energy. Several techniques have been suggested to improve the efficiency of TENG, but these strategies often result in higher intricacy and manufacturing expenses. This study presents an interlayer structure that efficiently increases the surface contact area of TENG, consequently improving their output performance. Using this structure, a cost-effective, highly sensitive, and easily manufacturable sensor called the Ecoflex-encapsulated interlayered triboelectric nanogenerator (EI-TENG), has been developed. The EI-TENG demonstrates superior performance compared to a monolayer TENG (M-TENG) of identical dimensions, exhibiting a 1.6-fold increase in voltage output, a fivefold enhancement in minimum measurement precision, and a 2.29-fold increase in sensitivity. In addition, the EI-TENG exhibits exceptional endurance, as it maintains a consistent output even after undergoing 10,000 cycles. Furthermore, it reliably functions under different temperature and humidity situations. The energy produced by the EI-TENG is adequate to power 45 LED lamps directly. The EI-TENG, when affixed to an athlete’s hand, is capable of sensing the distribution of pressure while dribbling and shooting a ball, which assists athletes in honing their methods and making necessary adjustments to their hand strength. This study not only demonstrates the creation of interlayer-structured TENG, which produces a high amount of electrical energy and is durable and stable in many environments, but also provides valuable information for the future advancement of affordable, self-sustaining electronic devices.